1984
DOI: 10.1128/jb.158.2.683-688.1984
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular siderophores from Aspergillus ochraceous

Abstract: A large number of iron-chelating compounds (siderophores) were isolated from supernatants of irondeficient cultures of a mold isolate, subsequently identified as Aspergillus ochraceous. Siderophores in their iron chelate form were purified to homogeneity by using Bio-Gel P2, silica gel, and C-18 bonded silica gel (reverse-phase) columns. Most of these compounds, as identified by 'H and 13C nuclear magnetic resonance spectroscopy and X-ray crystallography, belong to the ferrichrome family. The organism produces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Using the two asperchromes which had been previously isolated from A. ochraceus by van der Helm et al [3] we were able to demonstrate that the number of branched‐chain trans ‐anhydromevalonyl residues is also an important factor for recognition and transport by the Arn1p. Compared to ferrirubin, possessing three trans ‐anhydromevalonyl (AMV) residues, asperchrome B1 contains two AMV and one acetyl residue, while asperchrome D1 contains one AMV and two acetyl residues as shown in Fig.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Using the two asperchromes which had been previously isolated from A. ochraceus by van der Helm et al [3] we were able to demonstrate that the number of branched‐chain trans ‐anhydromevalonyl residues is also an important factor for recognition and transport by the Arn1p. Compared to ferrirubin, possessing three trans ‐anhydromevalonyl (AMV) residues, asperchrome B1 contains two AMV and one acetyl residue, while asperchrome D1 contains one AMV and two acetyl residues as shown in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…While ferrichrysin shares the same ser‐ser‐gly cyclic peptide sequence with ferrirubin, ferrirhodin and ferrichrome A, it is still excluded by the Arn1 transporter. Additional proof of this observation comes from studies with DDF, a ferrirhodin analog lacking a cyclic backbone which has been found as a natural byproduct in siderophores from A. ochraceus [3]. Although ferric DDF was not well transported by the wild type, it was excluded by the disruptant, confirming that branched‐chain N ‐acyl residues need to interact with the Arn1 transporter even in the absence of any peptide backbone.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Aspergillaceae family members are known to be a good source of various siderophores (4,17,23). Recently, a large number of asperchromes all belonging to the ferrichrorne family were isolated from low-iron cultures of Aspergillus ochraceus (11).…”
mentioning
confidence: 99%